Inculcating entrepreneurship through communication skills / Soo Kum Yoke ... [et al.] - Soo, Kum Yoke; Zainon, Saunah; Rajendran, Cecilia Bai; Kamaludin, Puteri Nur Hidayah (Universiti Teknologi MARA, Shah Alam: Malaysian Academy of SME and Entrepreneurship Development (MASMED), 2018)
Communication skills are essential for business and trading. However, young entrepreneurs in the school of business have often neglected this skill and viewed it as less important as opposed to their other core subjects offered at the university. Thus, this paper aims to investigate the importance of communication skills among young entrepreneurs in business schools at the university. This mixed method experimental study utilizes a digital story approach to language enhancement to enable clear communication. In order to do this, two business school classes at the university were treated with two separate treatments of the conventional approach and the digital story approach. The findings indicate that the digital approach promoted better communication among these young entrepreneurs. The study which is part of a more comprehensive study show that young entrepreneurs need to place importance in communication skills aside from their core subjects. For future studies, it is recommended that research on other skills besides communication skills can be investigated.